Autologous Islet Transplantation After Total Pancreatectomy for Renal Cell Carcinoma Metastases. Issue 9 (16th July 2013) - Gala‐Lopez, B. L.; Semlacher, E.; Manouchehri, N.; Kin, T.; Shapiro, A. M. J.
Abstract Pancreatic metastases from renal cell carcinoma (RCC) may have a chronic and highly indolent course, and may be resected for cure after considerable delay following treatment of the primary tumor, in contrast to other more common pancreatic tumors. Surgical resection is the treatment of choice, which may lead to postpancreatectomy diabetes mellitus in the case of extensive resection. We present a 70‐year‐old patient with multifocal pancreatic metastases from RCC causing obstructive jaundice. A total pancreatectomy was required to excise two distant tumors in the head and tail of the pancreas, together with a segment VI liver resection. An autologous islet transplant (AIT) prepared from the central, uninvolved pancreas was carried out to prevent postpancreatectomy diabetes. The patient was rendered insulin‐free and remains so with excellent glycemic control for 1 year of follow‐up, and there is no evidence of tumor recurrence. The patient has been treated with adjuvant sunitinib to minimize risk of further recurrence. In conclusion, AIT after pancreatectomy may represent a useful option to treat patients with metastatic RCC. A critical component of this approach was dependent upon elaborate additional testing to exclude contamination of the islet preparation by cancerous cells.